Perancangan Smart Locker dengan Implementasi Sistem IoT dan Aplikasi Mobile Android - Fitri Elvira Ananda; Salsabila Haurameuthia; Dandun Widhiantoro; M. Iqbal Tejasumirat (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2023)
A locker is a storage facility that can be seen at several public facilities such as public swimming pools, a library, and sports facilities like a gymnasium. Most lockers at public facilities still use conventional locking techniques. This has a negative impact in terms of effectiveness, efficiency, and security. Therefore, a QR-Code-based system that is integrated with the android application has been created to function for monitoring availability, borrowing lockers, and opening and locking lockers through the android application. Smart locker system using ESP32 as microcontroller and network that used to receive data sent from android application. When data is received, ESP32 will respond by activating the relay which controls the magnetic lock that replaced the conventional lock, while the android application is created for monitoring locker availability, borrowing lockers, and opening and locking lockers through the android application. This test is carried out for this application, which refers to the ISO 25010 standard with aspects of functional suitability, usability, and compatibility. The results of testing aspects of functional suitability and compatibility get 100 percent feasibility percentage results. Then for usability, it shows that from the 10-point questionnaire distributed to respondents, the percentage of feasibility results is 78.98 percent which is included in the acceptable category, this shows that the mobile application has good quality. The system test was done by pressing the button in the android application at the same time with two different devices and having a time difference while opening the lockers with a time average of 0.874 seconds.